2019
DOI: 10.1017/s1431927619000527
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of the Distribution of Cellulose Nanomaterial Aggregates in Composites Enabled by Multi-Channel Spectral Confocal Microscopy

Abstract: There is increased interest in the use of cellulose nanomaterials for the mechanical reinforcement of composites due to their high stiffness and strength. However, challenges remain in accurately determining their distribution within composite microstructures. We report the use of a range of techniques used to image aggregates of cellulose nanocrystals (CNCs) greater than 10 µm2 within a model thermoplastic polymer. While Raman imaging accurately determines CNC aggregate size, it requires extended periods of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Several studies have reported the analysis of the CNC distribution by Raman intensity maps based on the characteristic Raman bands located at ca . 1092 cm –1 . ,, However, the signaling peaks of polymer matrices are also located in the fingerprint region (400–1800 cm –1 ), inducing multiple Raman peak interference. Specifically, the Raman spectrum of HPC in the glycosidic linkage range 1000–1250 cm –1 coincides with the characteristic peaks of CNCs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the analysis of the CNC distribution by Raman intensity maps based on the characteristic Raman bands located at ca . 1092 cm –1 . ,, However, the signaling peaks of polymer matrices are also located in the fingerprint region (400–1800 cm –1 ), inducing multiple Raman peak interference. Specifically, the Raman spectrum of HPC in the glycosidic linkage range 1000–1250 cm –1 coincides with the characteristic peaks of CNCs .…”
Section: Resultsmentioning
confidence: 99%
“…Univariate analyses are usually adopted in a binary or ternary composite system, which requires a constituent-specific spectral band free of interference from other system constituents. Several recent studies reported the qualitative analysis of the stress transfer effect in CNC-reinforced composites by Raman spectroscopy, based on the characteristic of cellulose itself ( ca . 1095 cm –1 ).…”
mentioning
confidence: 99%
“…Previous research has confirmed that SCLSM can be used to identify cellulose aggregates in composite materials without the need for a fluorescent dye (Johns et al 2019). Here we confirmed the autofluorescence of microfibrillated cellulose (MFC), tannic acid (TA) and the MFC-TA-C 18 filler in composites.…”
Section: Sclsm Spectramentioning
confidence: 93%
“…2,25,26 The autofluorescence of poly-and oligo-saccharides, from various sources, has previously been widely reported. 6,[27][28][29][30][31][32][33][34][35] This autofluorescence is generally attributed to contamination of the sample with aromatic compounds, i.e. lignin, or proteins, dependent on the source.…”
Section: Introductionmentioning
confidence: 99%
“…We previously took advantage of this phenomenon to track the dispersion of cellulose particles in polymer matrices, confirming that the observed autofluorescence was intrinsically linked to the presence of cellulose. 6,31 In relation to cellulosic nanomaterials with typical surface chemical modifications, Li et al investigated the autofluorescent properties of carboxymethylated nanocellulose. 33 They demonstrated that the particles exhibited two fluorescent bands with an approximate wavelength difference of 40 nm, the second of which increased with concentration.…”
Section: Introductionmentioning
confidence: 99%